Main Aspects of Forming Speech Structures in Foreign Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Recently, the issue of forming speech structures in foreign language teaching has become one of the essential areas of modern linguistics and pedagogy. The study analyzes the main aspects of developing communicative and structural components of speech, emphasizing the integration of grammatical, lexical, and phonetic units in real communicative contexts. The research also explores innovative teaching methods and interactive approaches that enhance students’ ability to construct coherent and contextually appropriate speech patterns in English and other foreign languages.